Search for supersymmetry in multijet events with missing transverse momentum in proton-proton collisions at 13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
A search for supersymmetry is presented based on multijet events with large missing transversemomentum produced in proton-proton collisions at a center-of-mass energy of ffiffis p ¼ 13 TeV. The data,corresponding to an integrated luminosity of 35.9 fb−1, were collected with the CMS detector at the CERNLHC in 2016. The analysis utilizes four-dimensional exclusive search regions defined in terms of thenumber of jets, the number of tagged bottom quark jets, the scalar sum of jet transverse momenta, and themagnitude of the vector sum of jet transverse momenta. No evidence for a significant excess of events isobserved relative to the expectation from the standard model. Limits on the cross sections for the pairproduction of gluinos and squarks are derived in the context of simplified models. Assuming the lightestsupersymmetric particle to be a weakly interacting neutralino, 95% confidence level lower limits on thegluino mass as large as 1800 to 1960 GeV are derived, and on the squark mass as large as 960 to 1390 GeV,depending on the production and decay scenario.